Analysis of injuries in long-distance triathletes - Egermann, M.; Brocai, D.; Lill, C. A.; Schmitt, H. (International Journal of Sports Medicine, 2003)
Triathlon is an individual sport consisting of three disciplines - swimming, cycling and running. Triathlon has changed from a novel appearance to a very popular Olympic sport within the last fifteen years. Nevertheless, there is not sufficient data about injuries in triathlon. The aim of this retrospective survey was to investigate the incidence of injuries according to class of injuries, anatomical sites and disciplines. Relations to age, sex, performance level, training habits and medical care were analysed. Questionnaires were sent to all German speaking participants of the Ironman Europe 2000. With a response rate of 35 %, 656 questionnaires met the inclusion criteria. At least one injury was experienced by 74.8 % (95 %-CI: 71.3-78.1) of all respondents during their active time in triathlon. 51.1 % (95 %-CI: 47.2-55.0) suffered one or more contusion/skin-abrasions, 33.1 % (95 %-CI: 29.5-36.8) muscle-/tendon-injuries, 29.0 % (95 %-CI: 25.5-32.6) ligament-/capsule-injuries and 11.9 % (95 %-CI: 9.5-14.6) fractures. Most of the injuries happened during cycling (54.8 % [95 %-CI: 51.9-57.8]) within training sessions. 18.7 % (95 %-CI: 16.4-21.2) of all injuries occurred while the athletes were competing. Considering the low number of competition hours per year, the incidence of injuries during competition was higher than during training session. Significant relations were found considering the age, performance level and weekly training hours of the triathletes. Older athletes sustained more fractures (p = 0.024), high performance athletes suffered more contusions/abrasions (p = 0.003) and muscle-tendon-injuries (p = 0.001) and athletes with a large number of weekly training hours suffered more muscle-tendon-injuries (p = 0.014). To summarize, injuries in triathlon seem to be related to age, performance level and weekly training hours, but not to sex, presence of training coach and medical care.